Core Competencies or a Competent Core? A Scoping Review and Realist Synthesis of Invasive Bedside Procedural Skills Training in Internal Medicine. (November 2017) - Brydges, Ryan; Stroud, Lynfa; Wong, Brian M.; Holmboe, Eric S.; Imrie, Kevin; Hatala, Rose
Abstract : Purpose: Invasive bedside procedures are core competencies for internal medicine, yet no formal training guidelines exist. The authors conducted a scoping review and realist synthesis to characterize current training for lumbar puncture, arthrocentesis, paracentesis, thoracentesis, and central venous catheterization. They aimed to collate how educators justify using specific interventions, establish which interventions have the best evidence, and offer directions for future research and training. Method: The authors systematically searched Medline, Embase, the Cochrane Library, and ERIC through April 2015. Studies were screened in three phases; all reviews were performed independently and in duplicate. The authors extracted information on learner and patient demographics, study design and methodological quality, and details of training interventions and measured outcomes. A three-step realist synthesis was performed to synthesize findings on each study's context, mechanism, and outcome, and to identify a foundational training model. Results: From an initial 6, 671 studies, 149 studies were further reduced to 67 (45%) reporting sufficient information for realist synthesis. Analysis yielded four types of procedural skills training interventions. There was relative consistency across contexts and significant differences in mechanisms and outcomes across the four intervention types. The medical procedural service was identified as an adaptable foundational training model. Conclusions: The observed heterogeneity in procedural skills training implies that programs are not consistently developing residents who are competent in core procedures. The findings suggest that researchers in education and quality improvement will need to collaborate to design training that develops a "competent core" of proceduralists using simulation and clinical rotations. Abstract : Supplemental Digital Content is available in the text.